Suitability of virtual prototypes to support human factors/ergonomics evaluation during the design - Aromaa, Susanna; Väänänen, Kaisa (Applied ergonomics, 2016)
In recent years, the use of virtual prototyping has increased in product development processes, especially in the assessment of complex systems targeted at end-users. The purpose of this study was to evaluate the suitability of virtual prototyping to support human factors/ergonomics evaluation (HFE) during the design phase. Two different virtual prototypes were used: augmented reality (AR) and virtual environment (VE) prototypes of a maintenance platform of a rock crushing machine. Nineteen designers and other stakeholders were asked to assess the suitability of the prototype for HFE evaluation. Results indicate that the system model characteristics and user interface affect the experienced suitability. The VE system was valued as being more suitable to support the assessment of visibility, reach, and the use of tools than the AR system. The findings of this study can be used as a guidance for the implementing virtual prototypes in the product development process. •Both AR and VE prototypes support the assessment of human factors/ergonomics during the design.•The VE system was more suitable to support the assessment of visibility, reach, and the use of tools than the AR system.•System model characteristics can impact the suitability of the virtual prototype for the HFE evaluation.•To assess HFE issues related to environment, force and time, more sensory modalities are required.